KAJIAN PIDANA KERJA SOSIAL DITINJAU DARI SEGI SOSIOLOGI HUKUM - Bheti Widyastuti (HUKUM PEMBANGUNAN EKONOMI, 2020)
AbstractIn the application of Criminal Law in Indonesia, it uses a model of imprisonment. Imprisonment  penalties are often used because they are considered effective in providing a deterrent effect on criminals. However, along with the development of the times, imprisonment sanctions are considered not to prioritize the human side concerning the right to freedom for every human being. In the Draft Draft Criminal Code 2017 alternative sanctions were prepared. One of the alternative sanctions that will be discussed by the author is social work criminal sanctions. Social work criminal sanctions are considered in accordance with current criteria which prioritize the human side and provide direct moral learning to criminals. So that the author here aims to discuss the application of social work criminal sanctions in Indonesia from a criminal law perspective and the application of social work sanctions from a sociological legal perspective.AbstrakDalam penerapannya Hukum Pidana di Indonesia menggunakan model penjatuhan sanksi  pidana penjara. Sanksi pidana penjara sering kali digunakan karena dinilai efektif dalam memberikan efek jera bagi pelaku kejahatan. Namun seiring dengan perkembangan zaman sanksi pidana penjara dinilai tidak mengedepankan sisi kemanusian yang menyangkut hak merdeka bagi setiap manusia. Dalam Draft RUU KUHP 2017 disusunlah alternatif sanksi. Salah satu alternatif sanksi yang akan dibahas oleh penulis adalah sanksi pidana kerja sosial. Sanksi pidana kerja sosial dinilai sesuai dengan kriteria zaman saat ini yang lebih mengedepankan sisi kemanusiaan dan memberikan pembelajaran moral secara langsung kepada pelaku kejahatan. Sehingga penulis disini bermaksud untuk membahas penerapan sanksi pidana kerja sosial di Indonesia dari perspektif hukum pidana dan penerapan sanksi kerja sosial dari perspektif sosiologi hukum.